EVOLUTION OF MATERIALS FOR BALDRICS - KUZINA, NATALIA; KERNESH, VIKTORIiA; CHERTENKO, LILiIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
A baldric is a functional product and an important element of modern costume with a long history. The design, production technologies, and materials used have changed throughout historical development, leading to the improvement of products and increased requirements for their characteristics. Modern requirements for baldrics are dictated by their purpose, operating conditions, and environmental requirements for production. These factors are decisive in the selection of materials, which are represented by four main groups: natural leathers, textiles, synthetic leathers, and the latest biological materials. In the research process, methods of analysis, synthesis, and systematization were used to organize the data obtained according to specified criteria. The result of the work is a classification of baldric products and the requirements for materials for their manufacture; a chronological table of the evolution of materials for baldrics and their characteristics, and a comparative table of the characteristics of modern materials from the standpoint of compliance with operational, environmental, technological, and other requirements.  The baldric, once exclusively a functional element of military equipment, has today become an iconic accessory in the world of fashion, design, and functional use. Its transformation from a utilitarian product into a vivid expression of style demonstrates not only a change in functions but also an evolution of the materials used for its manufacture. At a time when innovations in production, environmental awareness, and new approaches to design play a key role, the study of baldrics becomes relevant for many areas – from the fashion industry to technology and the military.  The current relevance of the topic is also due to the fact that baldrics are actively returning to the collections of famous designers (Alexander McQueen, Louis Vuitton), and are also used in creative industries as a symbol of individuality and style. In addition, the interest in the restoration of historical artifacts and the introduction of environmentally friendly materials requires an understanding of how the materials for making baldrics have changed in different periods. Analysis of historical materials allows us to: determine changes in the functional purpose and design of products; trace the evolution of production technologies; adapt the best historical solutions to modern needs; and ensure a balance between aesthetics, comfort, and functionality of modern products.
Keywords: adaptive footwear; design; transformation of the source of inspiration; technology; production; transformative shaping